Arduino Uno Self-Drive Car: Design, Fabrication, and Experimental Evaluation (International Journal of Communication Systems and Network Technologies, 2020)
The advent of autonomous vehicles has spurred innovation in self-driving technologies, making them more accessible to hobbyists and enthusiasts. This paper presents the design, fabrication, and experimental evaluation of an Arduino Uno-based self-drive car. The system incorporates a variety of sensors, including ultrasonic distance sensors and infrared sensors, to perceive the environment. The Arduino Uno microcontroller is employed for real-time data processing and decision-making, utilizing a custom-developed control algorithm. The methodology encompasses the integration of hardware components and the development of software modules to achieve autonomous navigation. The experimental evaluation involves rigorous testing in controlled environments, assessing the self-drive car’s performance in obstacle avoidance, path following, and responsiveness to dynamic scenarios. Results indicate promising outcomes, demonstrating the feasibility of implementing a costeffective self-drive car using widely available components. The system exhibits robust obstacle detection capabilities and precise navigation, laying the groundwork for further enhancements and applications. The paper contributes to the growing body of knowledge in DIY autonomous systems and serves as a valuable resource for enthusiasts and researchers alike.
Keywords: Ardunio Uno; Self-drive Car; Autonomous Vehicles; Obstacle Avoidance; Experimental Evaluation